Agricultural Income Determinants among Smallholder Farmers: Case of Northern Part of Burundi - Nzabakenga, Alfred; Feng, Luo Xiao; Yaqin, He (Asian Journal of Agriculture and Rural Development, 2013)
About 90 percent of Burundi population depends on agriculture for their livelihoods. Agriculture employs the majority of labor force and is the basis source of income particularly for people living in rural areas. Agricultural income determines the purchasing power of many people living in rural areas. It is therefore important to examine the -determinants of agricultural income for proper policy formulation that will help to improve welfare of farmers. The main objective of this study is to analyze the determinants of agricultural income among smallholder farmers in Northern part of Burundi. Based on field survey which covered 218 respondents and using linear regression, we found that among 8 variables used in the analysis, only the family size and the farm size have shown significant effects on agricultural income at 1% and 10% levels respectively. Some suggestions were also mentioned to sustain the agricultural returns, the well-being of farm households and to improve the rural infrastructure.